Binding Constants of Mercury and Dissolved Organic Matter Determined by a Modified Ion Exchange Technique - Dong, Wenming; Bian, Yongrong; Liang, Liyuan; Gu, Baohua (Environmental science & technology, 2011)
Ion-exchange techniques have been widely used for determining the conditional stability constants (logK) between dissolved organic matter (DOM) and various metal ions in aqueous solution. An exception is mercuric ion, Hg2+, whose exceedingly strong binding with reduced sulfur or thiol-like functional groups in DOM makes the ion exchange reactions difficult. Using a Hg-selective thiol resin, we have developed a modified ion-exchange technique which overcomes this limitation. This technique allows not only the determination of binding constants between Hg2+ and DOM of varying origins, but also the discrimination of complexes with varying coordination numbers [i.e., 1:1 and 1:2 Hg:thiol-ligand (HgL) complexes]. Measured logK values of four selected DOM isolates varied slightly from 21.9 to 23.6 for 1:1 HgL complexes, and from 30.1 to 31.6 for 1:2 HgL2 complexes. These results suggest similar binding modes that are likely occurring between Hg2+ and key thiolate functional groups in DOM particularly at a relatively low Hg to DOM ratio. Future studies should further elucidate the nature and precise stoichiometries of binding between Hg2+ and DOM at environmentally relevant concentrations.